Digital Transformation and The Dynamics of School Culture In Indonesian Madrasah Ibtidaiyah - Ali Imron (Jurnal Pendidikan Educandum, 2026)
The digital era has brought significant transformations to education, including in Madrasah Ibtidaiyah. Teachers are required to enhance their technological competence, instructional innovation, and the reinforcement of students’ Islamic character. Digital transformation presents substantial challenges in delivering optimal educational services, particularly in integrating technology into the teaching and learning process. This study aims to identify the challenges faced by Madrasah Ibtidaiyah teachers in the digital era using a qualitative descriptive method through a literature review. The findings indicate that the primary challenges include limited infrastructure and facilities, insufficient continuous professional development, low student interest in academic literacy, and the underutilization of digital-based learning media. Teachers face multidimensional challenges encompassing technological, professional, and literacy-cultural aspects. Therefore, improving the quality of education in Madrasah Ibtidaiyah requires comprehensive efforts through adaptive training programs and adequate infrastructure provision to ensure that learning becomes more effective, engaging, and relevant to contemporary demands, while maintaining teachers’ roles as moral exemplars who guide students in the responsible use of technology.